OTENTISITAS REKONTRUKSI HISTORIS TRANSFORMASI HUKUM WARIS ISLAM DAVID S. POWERS - Aisah, Aisah; Sukardi, Imam (Prodi Ahwal al-Syakhsiyah STAI Darussalam Nganjuk, 2023)
The authenticity of the Quran and Sunnah is a controversial issue among Islamic studies scholars, and the answer to this question is a complex topic related to religious sensitivity. David Powers' research on the authenticity of the Islamic law of inheritance in his work